Physical properties of Mesozoic sedimentary rocks from the Perth Basin, Western Australia - Delle Piane, C.; Esteban, L.; Timms, Nicholas Eric; Ramesh Israni, S. (Taylor & Francis Co Ltd, 2013)
The Perth Basin (PB) hosts important aquifers within the Yarragadee Formation and adjacent geological formations with potential for economic exploitation by both geothermal energy and carbon capture and sequestration. Published studies on the reservoir quality of the sedimentary units of the PB are very few. This study reports some petrophysical and lithological characteristics of the sedimentary units of interest for geothermal and geosequestration scenarios and help interpolation toward non-sampled intervals. A new fluvial-dominated lithofacies scheme was developed for the Mesozoic stratigraphy from four wells drilled in the central PB (Pinjarra-1, Cockburn-1, Gingin-1 and Gingin-2) based on grainsize, sorting, sedimentary structures and colour that relate to the environment of deposition. Systematic laboratory measurements of permeability, porosity, and thermal conductivity were conducted on core samples to investigate a variety of lithofacies and depths from these wells. Empirical correlations are established among the different physical properties, indicating encouraging relationships for full PB basin interpolation such as between porosity and permeability, when the samples are grouped into ‘hydraulic units’ defined by a ‘flow zone indicator’ parameter. The common principal controls on the PB thermal conductivity are the pore space arrangement and mineralogical content, which are strongly lithofacies-specific. Therefore, the lithofacies type could be a good first-order discriminator for describing spatial variations of thermal conductivity and then estimate their flow zone indicator.